Determinants of related and unrelated export diversification - Muhammad Ali (Friedrich Schiller University Jena, 2016)
This paper contributes to the literature on determinants of export diversification by introducing related variety (RV) and unrelated variety (UV) in the analysis in addition to the traditional entropy based measure at three-digit SITC level, overall variety (OV). RV measures variety in cognitively related industries, while UV measures variety in industries that are unrelated to each other. Studies on RV and UV have shown that the dynamics of their relationship with economic growth and innovation may differ and one would expect that the determinants of RV and UV may also be different. Therefore, using data on manufacturing sector exports for 130 countries from 1996 to 2011, this paper analyzes the determinants of export diversification with primary focus on foreign direct investment as an external source of knowledge and a stimulus to entrepreneurship and human capital as a measure of productive capabilities. Considering the concern of endogeneity bias, estimations of the econometric models were performed using generalized method of moments. Findings show that the determinants of variety have different effects for different types of variety. The size of an economy and its trade openness significantly and positively affect all three types of diversification. Results also show that FDI negatively affects RV while there is no significant relationship with OV and UV. Moreover, interaction of human capital with FDI appears to be positive and significant for UV and RV while interaction of human capital with openness only appears to be significant and positive for RV showing the importance of knowledge through external sources in the process of diversification.
Keywords: F14; F21; O33; 330; export diversification; foreign direct investment; generalized method of moments; human capital; related variety; unrelated variety